Method for measuring corrosion of rebar in concrete, conductive adhesive gel, measuring probe
By using electrolyte gel on the measurement probe, the problem of difficulty in stable contact of the probe in the concrete structure is solved, and the stable holding of the probe and the accuracy of measurement is improved.
Patent Information
- Application Number
- JP2024104848
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2044-06-28
AI Technical Summary
In the prior art, when measuring steel bar corrosion in concrete structures, it is difficult for the measuring probe to maintain contact with the concrete structure stably, resulting in large workloads and unstable measurements.
Using a measuring probe with an electrolyte gel, the electrolyte gel has a water-absorbing resin and a modified propylene cross-linked polymer to form a paste-like fluidity. The adhesion of the probe remains stable through the gel after contacting the concrete structure.
The measurement probe is achieved stably held in the concrete structure, reducing operating workloads and improving measurement stability and accuracy.
Smart Images

Figure 0007671035000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for measuring corrosion of reinforcing bars in concrete, a conductive adhesive gel, and a measurement probe for measuring the state of corrosion of reinforcing bars in a concrete structure. [Background technology]
[0002] With the current cries of deterioration of infrastructure facilities in Japan, concrete structures are in urgent need of measures to deal with structures that are deteriorating. It is becoming increasingly recognized that preventive maintenance measures that take measures before deterioration-related changes become apparent are effective in reducing the costs of maintaining concrete structures. Therefore, since 2014, laws and regulations have stipulated that inspections based on close visual inspections must be conducted once every five years by people with the knowledge and skills. This close visual inspection is effective in grasping the soundness of concrete structures where cracks and other changes have become apparent, but if measures need to be taken before changes become apparent, a diagnosis based on the results of close visual inspections may be too late.
[0003] Generally, the pore water in concrete is strongly alkaline with a pH of 12 to 13, and iron forms a passive film on its surface, making it difficult for it to corrode. However, when the corrosion rate of reinforcing bars increases due to the effects of chloride ions that enter from the outside as a result of neutralization of concrete or salt damage, the corrosion of the reinforcing bars causes cracks in the concrete (hereafter referred to as corrosion cracks). The more corrosion of the reinforcing bars progresses, the more time and money it will take to repair or reinforce the concrete, so for efficient maintenance, it is important to understand the corrosion of the reinforcing bars before corrosion cracks occur.
[0004] Therefore, various non-destructive testing techniques have been developed that use alternating current to pass through reinforcing bars inside concrete to inspect the state of corrosion of the internal reinforcing bars without destroying the concrete structure and without relying on corrosion cracks (see, for example, Patent Document 1). In such non-destructive testing, it is necessary for an operator to contact a measurement probe (electrodes, sensors, etc.) with the outer wall (surface) of a concrete structure using his / her hand or a sensor support leg (see Non-Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 7113419 [Non-patent literature]
[0006] [Non-Patent Document 1] https: / / www.rex-rental.jp / large / 030 / middle / 090 / product / 20569
[0007] However, when using non-destructive testing to inspect the corrosion condition of rebar inside a concrete structure, it is necessary to keep a measurement probe (electrode, sensor, etc.) in stable contact with the concrete structure until the inspection is completed, and manually touching and holding the measurement probe is a heavy workload.
[0008] Furthermore, when the measurement probe is supported on the underside of a concrete structure for inspection by the sensor support legs, the sensor support legs must be installed in a stable location. Therefore, when inspecting the underside of a bridge from a rocking ship on the sea surface, it is difficult to hold the measurement sensor stably using the sensor support legs. Therefore, there is a need for a technique that enables a measurement probe to be held stably and reduces the workload involved in the measurement process when measuring the corrosion state of reinforcing bars inside a concrete structure. Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been devised based on the above-mentioned conventional problems and proposals, and aims to provide a technology that enables a measurement probe to be stably held on a concrete structure and reduces the workload involved in measuring the corrosion condition of reinforcing bars inside a concrete structure. [Means for solving the problem]
[0010] The present invention relates to A method for measuring corrosion of rebar in concrete, comprising: A conductive adhesive gel containing a supporting electrolyte aqueous solution and a water-absorbent resin and having a fluidity similar to starch paste is applied to the electrodes of the measurement probe; Concrete Structures a conductive adhesive gel is filled into the recess to bring the electrode into close contact with the concrete structure and to adhere and hold the measurement probe to the concrete structure; measuring a corrosion state of the reinforcing steel in the concrete structure by passing an AC current through the electrodes to the reinforcing steel in the concrete structure; It is characterized by: or A method for producing a conductive adhesive gel used in a method for measuring corrosion of reinforcing bars in concrete, comprising: A water-absorbent resin, which acts as a gelling agent, is added to the aqueous solution of the supporting electrolyte. A conductive adhesive gel with starch paste-like fluidity is produced by stirring and kneading the supporting electrolyte aqueous solution to which the water-absorbing resin has been added. It is characterized by: or A conductive adhesive gel for use in a method for measuring corrosion of reinforcing bars in concrete, comprising: The water-absorbent resin contains a modified acrylic crosslinked polymer and has a starch paste-like fluidity. It is characterized by: or The water-absorbent resin is AQUALIC CS-8S (registered trademark, manufactured by Nippon Shokubai Co., Ltd.), which contains a modified acrylic crosslinked polymer. It is characterized by: or The total weight of the measurement probe equipped with the electrodes is W (kg), and the contact area of the electrodes with the concrete structure is S (mm 2 ), then Strength T(N / mm 2 )≧9.8·(W(kg) / S(mm 2 )) is set to It is characterized by: or The total weight of the measurement probe is 60 x 10 -3 kg, the electrode connection surface is a circle with a diameter of 50 (mm), Strength T(N / mm 2 ) ≧ 0.3 × 10 -3 (N / mm 2 ) is set to It is characterized by: or A measurement probe for measuring a corrosion state of a reinforcing bar in a concrete structure by passing an electric current through the concrete structure, An electrode; a conductive adhesive gel containing a modified acrylic crosslinked polymer and having a starch paste-like fluidity; Equipped with The conductive adhesive gel is applied to the electrodes, and the conductive adhesive gel penetrates into and adheres to the recesses of the concrete structure, and the electrodes are adhered to and held by the concrete structure. It is characterized by the above. Effect of the Invention
[0011] According to the method for measuring corrosion of steel bars in concrete, the conductive adhesive gel, and the measurement probe of the present invention, the measurement probe is adhered and held to the concrete structure by the conductive adhesive gel, so that the measurement probe can be stably held to the concrete structure and the workload during the measurement work can be reduced. [Brief description of the drawings]
[0012] [Figure 1]FIG. 1 is a conceptual diagram for explaining an outline of a method for measuring corrosion of rebar in concrete according to a first embodiment of the present invention. [Diagram 2] FIG. 1 is a diagram illustrating a schematic configuration of a rebar corrosion measuring device in concrete according to a first embodiment. [Diagram 3] FIG. 2 is a diagram illustrating a schematic configuration of a corrosion measuring device main body according to the first embodiment. [Figure 4] 1A to 1D are diagrams illustrating a schematic configuration of a measurement probe according to a first embodiment, where (A) is a top view, (B) is a front view, (C) is a side view, and (D) is a bottom view. [Diagram 5] 4 is a flowchart illustrating a method for producing a conductive adhesive gel according to the first embodiment. [Figure 6] 1A to 1C are diagrams illustrating an example of a conductive adhesive gel according to a first embodiment. [Figure 7] 2A to 2C are diagrams illustrating properties of the conductive adhesive gel according to the first embodiment. [Figure 8] 4A to 4C are diagrams illustrating the adhesive strength of the conductive adhesive gel according to the first embodiment. [Figure 9] FIG. 1 is a conceptual diagram illustrating an example in which the in-concrete rebar corrosion measuring device according to the first embodiment is applied to a in-concrete rebar corrosion measuring method (AC impedance method). [Figure 10] FIG. 2 is a conceptual diagram illustrating a current-carrying state in the AC impedance method according to the first embodiment. [Figure 11] FIG. 1 is a conceptual diagram showing a state in which a measurement probe in a method for measuring corrosion of steel bars in concrete according to the first embodiment is adhered (attached) to a concrete structure, where (A) is a conceptual diagram showing an example of measurement from the bottom surface, and (B) is a conceptual diagram showing an example of measurement from the side surface. [Figure 12] FIG. 2 is a conceptual diagram illustrating a connection state in a three-electrode method according to the first embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] [First embodiment] A first embodiment of the present invention will now be described with reference to FIGS. Fig. 1 is a conceptual diagram for explaining an outline of a method for measuring rebar corrosion in concrete according to a first embodiment of the present invention, Fig. 2 is a diagram for explaining the outline of a rebar corrosion measuring device in concrete, and Fig. 3 is a diagram for explaining the outline of a corrosion measuring device main body. Also, Fig. 4 is a diagram for explaining the outline of a measuring probe, with Fig. 4(A) showing a top view, Fig. 4(B) showing a front view, Fig. 4(C) showing a side view, and Fig. 4(D) showing a bottom view when no conductive adhesive gel has been applied. In the figure, reference numeral 1 denotes a corrosion measuring device for steel bars in concrete, reference numeral 10 denotes the main body of the corrosion measuring device, reference numeral 20 denotes a measuring probe, reference numeral 22 denotes an electrode, reference numeral 26 denotes a conductive adhesive gel, and reference numeral C denotes a concrete structure. The measurement of rebar corrosion in concrete according to the first embodiment is exemplified by an AC impedance method.
[0014] 1, the method for measuring corrosion of rebars in concrete according to the first embodiment adheres a measurement probe 20 to the surface of a concrete structure C by the adhesiveness of a conductive adhesive gel, and holds the measurement probe 20 on the concrete structure C until the measurement is completed (for example, for about 15 minutes), and passes an AC current, thereby measuring the corrosion state of the rebars embedded in the concrete structure C. Note that various methods can be applied for measurement and determination methods (AC current frequency, current value, change in current value, etc.) in the AC impedance method.
[0015] Hereinafter, a schematic configuration of the in-concrete rebar corrosion measuring device 1 will be described with reference to FIG. As shown in Figure 2, the steel bar corrosion measuring device 1 in concrete includes, for example, a corrosion measuring device main body 10, three measuring probes (electrodes) 20, and cables (symbol 30 shown in Figure 1, not shown in Figure 2) connecting the corrosion measuring device main body 10 and each measuring probe (electrode) 20. The in-concrete rebar corrosion measuring device 1 is capable of measuring the corrosion state of the rebar, for example by applying an alternating current to a rebar buried inside a concrete structure C from its surface and calculating the impedance of the rebar surface.
[0016] 3, the corrosion measuring device main body 10 is equipped with, for example, a CE terminal 11CE, a RE terminal 11RE, a WE(pot) terminal 11WEp, and a WE(cur) terminal 11WEc, each of which can be connected to a cable. Furthermore, the CE terminal 11CE and the WE(cur) terminal 11WEc are connected, for example, to a counter electrode, and the RE terminal 11RE and the WE(pot) terminal 11WEp are connected, for example, to a reference electrode. As shown in FIG. 3, the corrosion measuring device main body 10 is equipped with an AC power supply 10P, a current measuring device (ammeter) 10A, and a potential difference measuring device (potentiometer) 10V. The AC power supply 10P and the current measuring device (ammeter) 10A are arranged in series between the CE terminal 11CE and the WE (cur) terminal 11WEc, and the potential difference measuring device (potentiometer) 10V is arranged between the RE terminal 11RE and the WE (pot) terminal 11WEp. The AC power supply 10P is capable of applying AC currents of various frequencies to the CE terminal 11CE and the WE (cur) terminal 11WEc, and the current measuring device (ammeter) 10A measures the current passing between the CE terminal 11CE and the WE (cur) terminal 11WEc. The potential difference measuring device (potentiometer) 10V is disposed between the RE terminal 11RE and the WE(pot) terminal 11WEp, and is configured to measure the potential difference between the RE terminal 11RE and the WE(pot) terminal 11WEp. With this configuration, the potential difference between the potential of the concrete structure and the potential approximately below the counter electrode is measured at the RE terminal 11RE and the WE(pot) terminal 11WEp. In addition, it is preferable that the corrosion measuring device main body 10 is equipped with a detection means (not shown) that determines the degree of impedance from the current value and potential difference value measured when each AC current is passed through, and detects corroded locations of the reinforcing bars in the concrete structure C based on the determined degree of impedance.
[0017] Furthermore, it is preferable that the corrosion measuring device main body 10 is powered, for example, from a PC (personal computer) or a mobile battery, and such a configuration makes it possible to eliminate the need for a large-scale power supply device and to reduce power supply noise. The system is configured to apply an appropriate voltage to the structure using a unique voltage control system, making it possible to obtain polarization resistance with high precision. The calculation format of the corrosion measuring device main body 10 can be set arbitrarily, and it is possible to apply it to various well-known rebar corrosion methods, for example, that determine the corrosion state of rebar by determining the potential of the rebar and the potential in the concrete structure C.
[0018] In addition, the corrosion measuring device main body 10 is preferably configured to calculate the polarization resistance by fitting an equivalent circuit through analysis of the measurement results, and to be able to calculate the corrosion rate per unit area by identifying the measured area using existing methods. If corrosion measuring device main body 10 can be directly connected to a reinforcing bar, WE(pot) terminal 11WEp and WE(cur) terminal 11WEc may be connected to the reinforcing bar and used for measurement by the three-electrode method.
[0019] As shown in FIG. 4, the measurement probe (electrode) 20 includes, for example, an electrode 22, a casing 24, and a conductive adhesive gel 26, and weighs, for example, 60 g (60×10 -3 The weight is set at 1 kg. The electrode 22 is made of, for example, aluminum, and includes an inner electrode portion (reference electrode) 22A which serves as a reference electrode, and an outer electrode portion (counter electrode) 22B which serves as a counter electrode. The inner electrode portion (reference electrode) 22A is formed in a generally cylindrical shape with a flat tip. The outer electrode portion (counter electrode) 22B is substantially disk-shaped with a circular through hole formed in the center, and the inner electrode portion (reference electrode) 22A is disposed in this circular through hole with a radial gap therebetween. Further, the tip surface of the inner electrode portion (reference electrode) 22A and the outer electrode portion (counter electrode) 22B are formed flush with each other. In this embodiment, the outer electrode portion (counter electrode) 22B is set to a circular shape with an outer diameter of, for example, 50 mm. In addition, a conductive adhesive gel 26, which will be described later, is applied to the tip surface of the inner electrode portion (reference electrode) 22A and the flat surface of the outer electrode portion (counter electrode) 22B.
[0020] The casing 24 is formed into a substantially rectangular parallelepiped. The electrode 22 is disposed on one end surface in the longitudinal direction, and the terminal 25 for connecting the cable 30 is disposed on the other end surface. Furthermore, wiring for connecting the electrode 22 and the terminal 25 is provided inside the casing 24. The side surface of the case where the electrodes 22 and terminals 25 are not arranged is formed to a size that can be gripped during operation.
[0021] The terminal 25 includes a first terminal portion 25A and a second terminal portion 25B. For example, the first terminal portion 25A is connected to the inner electrode portion (reference electrode) 22A, and the second terminal portion 25B is connected to the outer electrode portion (counter electrode) 22B. Further, the first terminal portion 25A and the second terminal portion 25B are connected to corresponding terminals of the cable 30.
[0022] The conductive adhesive gel 26 is placed between the electrode 22 and the surface of the concrete structure to pass electricity from the electrode 22 to the concrete structure in order to measure the corrosion rate of the reinforcing steel buried inside the concrete structure. The conductive adhesive gel 26 has an adhesive property (adhesive strength) that adheres and holds the measurement probe 20 to the surface of the concrete structure. Here, adhesiveness means that even if the gel solidifies or hardens over the long term, the adhesiveness is maintained within the measurement time range and the gel can be attached and removed. In addition, the measurement probe 20 weighs 60g (60×10 -3 kg) and the measurement time is, for example, 15 minutes (for example, 20 minutes including a margin), the tensile strength T of the conductive adhesive gel 26, for example, 20 minutes after the electrode 20 is adhered to the concrete structure, is Since the electrode is circular with a diameter of 50 mm, the machine connection area (adhesive area) is (πx25x25) (mm), so Strength T(N / mm 2 )≧9.8·(W(kg) / S(mm 2 )) 9.8×60×10 -3 / (Connection area)=9.8×60×10 -3 / (πx25x25)=0.3×10 -3 (N / mm 2 ) It is preferable to set it to
[0023] Next, the conductive adhesive gel 26 will be described with reference to FIGS. FIG. 5 is a flow chart illustrating an example of a method for producing (manufacturing) a conductive adhesive gel, and FIG. 6 is a diagram (photograph) illustrating an example of the conductive adhesive gel according to the first embodiment. The conductive adhesive gel 26 is produced by, for example, absorbing a 3.3 mol / L potassium chloride (KCl) aqueous solution, which is an aqueous solution of a supporting electrolyte, into a water-absorbing resin and kneading the resin.
[0024] Hereinafter, a method for producing (manufacturing) the conductive adhesive gel 26 will be described with reference to FIG. As shown in FIG. 5, the conductive adhesive gel 26 is produced by, for example, "preparing a potassium chloride (KCl) aqueous solution (aqueous supporting electrolyte solution) and a gelling agent" (S1), "adding the gelling agent to the potassium chloride (KCl) aqueous solution" (S2), and "stirring and kneading the potassium chloride (KCl) aqueous solution (aqueous supporting electrolyte solution) with the gelling agent added" (S3), through which "the conductive adhesive gel is produced" (S4).
[0025] (1) Prepare a potassium chloride (KCl) aqueous solution (supporting electrolyte aqueous solution) and a gelling agent (S1) Prepare a potassium chloride (KCl) aqueous solution (aqueous supporting electrolyte solution) and a gelling agent. As the aqueous supporting electrolyte solution, for example, a 3.3 mol / L aqueous potassium chloride (KCl) solution is suitable. The gelling agent may be any one that can secure a practical adhesive strength. Generally, a water-absorbing resin is less likely to absorb an aqueous solution containing salt, but it is desirable that the water-absorbing resin has salt resistance, can sufficiently absorb an aqueous solution of potassium chloride (KCl) (aqueous solution of a supporting electrolyte), and is less likely to form lumps (lumps of solid matter). For example, it is preferable to use a water-absorbing agent that contains a modified acrylic crosslinked polymer. The type and concentration of the electrolyte used in the aqueous supporting electrolyte solution may be set arbitrarily.
[0026] In addition, when a salt-resistant water-absorbing resin (e.g., AQUALIC CS-8S (registered trademark, manufactured by Nippon Shokubai Co., Ltd.) is used, the water absorption amount in artificial seawater is about 1.5 times that of a general water-absorbing agent, and sufficient water absorption is ensured, which is preferable. AQUALIC CS-8S, for example, has an average particle size of approximately 15 μm, and compared to AQUALIC CS-8HM, which has an average particle size of approximately 100 μm, it is more prone to clumping, but it is possible to ensure strong adhesive strength (stickiness), and clumps of a size that is harmful to adhesion are less likely to form.
[0027] (2) Adding a gelling agent to potassium chloride (KCl) (aqueous supporting electrolyte solution) (S2) Next, a gelling agent is added to an aqueous potassium chloride (KCl) solution (aqueous supporting electrolyte solution). The amount of addition may be set arbitrarily after confirming the required adhesive strength. In this embodiment, for example, 15 g of AQUALIC CS-8S (registered trademark) was added to 100 g of a 3.3 mol / L aqueous potassium chloride (KCl) solution (aqueous supporting electrolyte solution).
[0028] (3) A potassium chloride (KCl) aqueous solution (aqueous supporting electrolyte solution) to which a gelling agent has been added is stirred and kneaded (S3). An aqueous solution of potassium chloride (KCl) (aqueous supporting electrolyte solution) to which a gelling agent has been added is stirred and kneaded to create viscosity so that lumps do not form. The stirring may be performed manually or by using a mixer.
[0029] (4) Conductive adhesive gel is generated (S4) By carrying out the above steps S1 to S3, a conductive adhesive gel is produced.
[0030] The conductive adhesive gel 26 produced by the above manufacturing method has fluidity (viscosity) similar to that of starch paste used in crafts and office work, as shown in Figure 6, and can be free of lumps that would prevent the electrode 22 from adhering to the surface of the concrete structure 22. Furthermore, for example, after being adhered to the surface of the concrete structure C, the adhesiveness is maintained at least until the measurement work is completed (for example, about 15 minutes), so that the measurement probe 20 can be adhered and held to the outer wall surface of the concrete structure C by the adhesiveness.
[0031] Furthermore, the conductive adhesive gel 26 is applied to the surface of the electrode 22 in a substantially flat manner before measurement. Note that the flatness means that when the electrode 22 is pressed against the concrete structure C, the conductive adhesive gel 26 is compressed and deformed so that the electrode 22 faces the surface of the concrete structure C with the conductive adhesive gel 26 sandwiched therebetween to an extent that electricity can be conducted therebetween. Furthermore, the thickness of the conductive adhesive gel 26 is preferably such that, if the surface of the concrete structure C is uneven, the conductive adhesive gel 26 can penetrate into the recesses and the surface of the electrode 22 can face the concrete structure C approximately parallel to the concrete structure C.
[0032] Next, a suitable amount of additive when producing a conductive adhesive gel using AQUALIC CS-8S (registered trademark) will be described with reference to FIG. 7 and FIG. To confirm the amount added, AQUALIC CS-8S (registered trademark) was added to 100 g of a 3.3 mol / L aqueous potassium chloride (KCl) solution (aqueous supporting electrolyte solution), and the aqueous potassium chloride (KCl) solution (aqueous supporting electrolyte solution) was stirred into AQUALIC CS-8S (registered trademark) to cause it to absorb water and knead to produce a conductive adhesive gel. The properties of this gel were confirmed, and the adhesive strength was measured. The amounts of AQUALIC CS-8S (registered trademark) added were 5 g, 10 g, 15 g, 20 g, and 25 g.
[0033] The adhesive strength was measured by attaching a φ50mm diameter electrode plate coated with conductive adhesive gel to a horizontal flat surface of concrete, then pulling the electrode plate in a direction perpendicular to the adhesive surface (vertical direction) and measuring the adhesive strength against tension in the direction perpendicular to the adhesive surface. Measurements were performed three times for each conductive adhesive gel. The results are shown in Figures 7 and 8.
[0034] The properties and adhesive strength of the conductive adhesive gel will be described below with reference to Fig. 7 and Fig. 8. Fig. 7 is a diagram for explaining the properties of the conductive adhesive gel according to the first embodiment, and Fig. 8 is a diagram for explaining the adhesive strength of the conductive adhesive gel. The conductive adhesive gel produced with an additive amount of 5 g was viscous and almost liquid, and as shown in Figure 8, the adhesive strength was approximately 0.4 × 10 -3 (N / mm 2 ) was. In addition, the conductive adhesive gel produced with an additive amount of 10 g was easy to apply, and the adhesive strength was approximately 1.30 to 1.79 × 10 -3 (N / mm 2 ) was. In addition, the conductive adhesive gel produced with an additive amount of 15 g was easy to apply and had an adhesive strength of approximately 1.34 to 1.68 × 10 -3 (N / mm 2 ) was. In addition, the conductive adhesive gel produced with an additive amount of 20 g was easy to apply, and the adhesive strength was approximately 1.34 to 1.60 × 10 -3 (N / mm 2 ) was. In addition, the conductive adhesive gel produced with an additive amount of 25 g was difficult to apply, but had an adhesive strength of approximately 1.08 to 1.20 × 10 -3 (N / mm 2 ) was.
[0035] For example, if the total weight of the measurement probe is 60 g, the required adhesive strength is 0.3 × 10 -3 (N / mm 2 ), it was confirmed that the adhesive strength was sufficient when the amounts added were 10g, 15g, and 20g. It was also confirmed that a practical level of adhesive strength could be secured even when the amount added was 25 g. On the other hand, it was found that an addition amount of 5 g was not suitable.
[0036] Next, referring to Figs. 9 to 11, an example of applying the in-concrete rebar corrosion measuring device 1 according to the first embodiment to a method of measuring rebar corrosion in concrete (AC impedance method) will be described. Fig. 9 is a conceptual diagram for explaining an example of applying the in-concrete rebar corrosion measuring device 1 and the conductive adhesive gel 26 according to the first embodiment to impedance measurement in the method of measuring rebar corrosion in concrete (AC impedance method), and Fig. 10 is a conceptual diagram for explaining a current-carrying state in the AC impedance method according to the first embodiment. Fig. 11 is a conceptual diagram showing an example of attachment (mounting) of a measurement probe. The AC impedance method is one of the methods of measuring rebar corrosion in concrete for grasping the corrosion state of rebar, and the conductive adhesive gel 26 is attached to the surface of a concrete structure C so that it can be electrically conductive, and is then used to obtain the potential, impedance, etc. for determining the corrosion state of the rebar by passing an AC current through the rebar.
[0037] In the method for measuring corrosion of rebars in concrete (AC impedance method) according to the first embodiment, an AC current is applied to rebars R in a concrete structure C from the surface of the concrete structure C using a rebar corrosion measuring device 1, for example, to calculate the polarization resistance (impedance) and measure the corrosion rate of the rebars. The conductive adhesive gel 26 may be applied to various measurement methods in which the measurement probe 20 is attached to the surface of the concrete structure C with the conductive adhesive gel 26 and an alternating current is applied.
[0038] The method for measuring rebar corrosion in concrete (AC impedance method) shown in Figures 9 to 11 involves applying AC currents of various frequencies using a rebar corrosion measuring device 1 in concrete, measuring the impedance, analyzing the obtained impedance spectrum, and calculating the polarization resistance, which is an indicator of rebar corrosion.
[0039] Various methods, such as the three-electrode method, can be used to obtain the impedance spectrum of reinforcing steel in concrete. In the three-electrode method, the measuring device is directly connected to the rebar, so all of the applied current flows through the rebar and the measurement results can be handled quantitatively, but it is necessary to remove part of the concrete structure to expose the rebar when making the measurement. On the other hand, in the method for measuring corrosion of rebar in concrete related to this method, the current flowing through the rebar becomes unclear and the measurement results are difficult to interpret, but there is no need to expose the rebar and the measurement can be performed non-destructively.
[0040] Hereinafter, an example of a method for measuring corrosion of rebar in concrete will be described with reference to Figs. [Measurement probe installation] First, as shown in FIG. 9, the measurement probe 20A, the measurement probe 20B, and the measurement probe 20C are placed on the surface of the concrete structure C corresponding to the reinforcing bar R. At this time, the measurement probes 20A, 20B, and 20C are arranged at an appropriate distance (for example, 130 cm or more) from each other so that electricity does not flow through the concrete structure C to each other. In addition, it is desirable to moisten the concrete structure C for, for example, 15 minutes or more before adhering the measurement probes 20 (20A, 20B, 20C).
[0041] Moreover, the measurement probes 20A, 20B, and 20C are connected to the measurement device body 10 of the in-concrete rebar corrosion measuring device 1 as shown in FIGS. Specifically, the measurement probe 20A is connected to the CE terminal 11CE and the RE terminal 11RE. At this time, as shown in FIG. 10, the outer electrode portion (counter electrode) 22B is connected to the CE terminal 11CE, and the inner electrode portion (reference electrode) 22A is connected to the RE terminal 11RE.
[0042] 9 and 10, the measurement probe 20B is connected to the RE terminal 11RE and the corresponding WE (pot) terminal WE p As a result, the inner electrode portion (reference electrode) 22A of the measurement probe 20B is connected to the inner electrode portion (reference electrode) 22A of the measurement probe 20A, which serves as the reference electrode, via the potential difference meter 10A.
[0043] 9 and 10, the measurement probe 20C is connected to the CE terminal 11CE and the corresponding WE (cur) terminal 11WE C As a result, the outer electrode portion (counter electrode) 22B of the measurement probe 20C is connected to the outer electrode portion (counter electrode) 22B of the measurement probe 20A via the AC power source 10P and the current measuring device 10A.
[0044] In addition, Figure 9 shows an example in which the reinforcing bar R is embedded on the upper side (near the upper surface) of the concrete structure C, but if the reinforcing bar R to be measured is embedded on the underside (near the underside) of, for example, a bridge, the measurement probe 20 is adhered to the underside of the concrete structure C as shown in Figure 11 (A). Furthermore, when the reinforcing bar R to be measured is embedded in the side portion (near the side) of a vertical wall of a bridge pier or embankment, for example, the measurement probe 20 is adhered to the side of the concrete structure C as shown in FIG. 11(B).
[0045] [Measurement method] Hereinafter, polarization resistance measurement by this method will be described with reference to FIG. In FIG. 10, symbols Z1, Z2, Z3 are the impedances from measurement probes 20A, 20B, 20C to the reinforcing bar, respectively, and impedances Z1, Z2, Z3 are composed of the resistance of the conductive adhesive gel 26 at each position and the resistance due to the concrete (hereinafter referred to as concrete resistance) R11, R21, R31, the electrical resistance R12, R22, R32 on the surface of the reinforcing bar R, and the capacitors C1, C2, C3 at the interface between the concrete and the reinforcing bar. In addition, by installing each measurement probe 20 (20A, 20B, 20C) at a position sufficiently far apart, no current flows directly through only the surface of the concrete structure C and the cover of the concrete structure C, and all current passing through the interior of the concrete structure passes through the reinforcing bars R. Specifically, between measurement probe 20A and measurement probe C, an AC current passes through the path of the outer electrode portion (counter electrode) 22B of measurement probe 20A, the inside of concrete structure C, the reinforcing bar R, the inside of concrete structure C, and the outer electrode portion (counter electrode) 22B of measurement probe 20C.
[0046] The specific steps are described below. (1) Alternating currents of various frequencies are applied between the inner electrode portion (reference electrode) 22A of the measurement probe 20A and the inner electrode portion (reference electrode) 22A of the measurement probe 20B. When the probes are sufficiently separated from each other, no current flows from the measurement probe 20A to the measurement probe 20B regardless of the frequency. Here, the dashed arrow with an x in Figure 10 indicates that no current flows. As a result, the change in the potential difference between the inner electrode portion (reference electrode) 22A of measurement probe 20B and the inner electrode portion (reference electrode) 22A of measurement probe 20A becomes equal to the potential difference applied to impedance Z1. At this time, an output is provided from measurement probe 20A so that the potential difference between measurement probe 20A and measurement probe 20B becomes a sine wave, and the current generated at this time is monitored by measurement probe 20C, thereby making it possible to obtain impedance Z1. (2) Next, in the equivalent circuit of impedance Z1, the concrete-reinforced concrete interface has capacitor C1 in parallel with electrical resistance R12, so in the high frequency range, only the concrete resistance R11 is measured, and in the low frequency range, the impedance of concrete resistance R11 + electrical resistance R12 is measured. Therefore, by measuring Z1 at various frequencies and fitting it to the equivalent circuit, electrical resistance R12 can be obtained. (3) Next, for example, the cover thickness CL, the diameter of the rebar R, the rebar spacing, etc. shown in Figure 9 are input to estimate the polarization resistance and corrosion rate. In healthy rebars, electrical resistance R12 is large, while in rebars with advanced corrosion, electrical resistance R12 is small.
[0047] From the above, in the polarization resistance measurement, the potential difference applied to Z1 is measured based on the voltage value at the reference electrode from the inner electrode portion (reference electrode) 22A of the measurement probe 20A via the conductive adhesive gel 26, and current is passed through the concrete structure C from the outer electrode portion (counter electrode) 22B of the measurement probe 20A via the conductive adhesive gel 26 to measure the current flowing through Z1 based on the current value at the counter electrode. The impedance Z1 is calculated by taking the ratio of these values, and the electrical resistance R12 is calculated by analyzing Z1 to determine the corrosion condition of the reinforcing bar R.
[0048] Any method may be used to estimate the corrosion state, and it is preferable to calculate the electrical resistance R12 by referring to, for example, the concrete cover of the reinforcing bar to be measured, the diameter of the reinforcing bar to be measured, and the spacing between the reinforcing bars. stomach. Incidentally, the above (1) and (2) are usually measured starting from high frequencies. The corrosion state of the reinforcing bar R may be measured at a plurality of measurement points by moving the measurement probe 20 (changing the position).
[0049] According to the method for measuring corrosion of rebar in concrete, the conductive adhesive gel 26, and the measurement probe 20 of the first embodiment, the measurement probe 20 is adhered and held to the concrete structure C by the conductive adhesive gel 26, so that the measurement probe 20 can be stably adhered and held to the concrete structure C, and manual holding is not required during the measurement work, thereby reducing the workload. Furthermore, since the measurement probe 20 is adhered to the concrete structure C by its adhesiveness, the measurement probe 20 can be easily removed after the measurement work is completed.
[0050] In addition, the measurement probe 20 is adhered and held to the concrete structure C due to its adhesiveness, so there is no need to support and hold the measurement probe 20 to the concrete structure C using a support member (rigid body) or manually.The measurement probe 20 is connected to the corrosion measuring device main body 10 by a cable 30, which increases the freedom of positioning of the measurement probe 20.As a result, it is possible to stably measure the corrosion condition of reinforcing bars R buried under the underside and near the sides of a bridge, even from a ship rocking on the sea surface or river surface.
[0051] In addition, since the conductive adhesive gel (conductive adhesive gel) 26 can be deformed to conform to the unevenness of the concrete structure C, the electrode 22 is in close contact with the concrete structure C, reducing the electrical resistance, allowing electricity to flow efficiently. Furthermore, since the measurement probe 20 can be stably held on the concrete structure C, the measurement accuracy can be improved.
[0052] Next, a method for measuring rebar corrosion in concrete using a three-electrode method according to a modified example of the first embodiment will be described with reference to Fig. 12. Fig. 12 is a conceptual diagram for explaining a connection state applied to the three-electrode method according to the modified example of the first embodiment. In measuring rebar corrosion in concrete using the three-electrode method, the WE(pot) terminal WEp and the WE(cur) terminal WEc of the corrosion measuring device main body 10 are directly connected to rebar R exposed from a concrete structure C, as shown in Fig. 12. The rebar R is exposed in advance by, for example, unscrewing (removing) the concrete structure C.
[0053] As shown in FIG. 12, in the corrosion measuring device main body 10, the RE terminal 11RE and the WE(pot) terminal WEp are connected via a potential difference meter, and the CE terminal 11CE and the WE(cur) terminal WEc are connected via an AC power supply 10P and a current meter 10A. Then, the measurement probe 20A (20) is placed on the surface (measurement surface) of the concrete structure C at a position corresponding to the reinforcing bar R to be measured. At this time, the inner electrode portion (reference electrode) 22A and the outer electrode portion (counter electrode) 22B of the measurement probe 20A are connected to the surface of the concrete structure C via the conductive adhesive gel 26. Moreover, an inner electrode portion (reference electrode) 22A of the measurement probe 20A (20) is connected to the RE terminal 11RE, and an outer electrode portion (counter electrode) 22B is connected to the CE terminal 11CE.
[0054] Then, an AC current in a low frequency range of, for example, 0.01 Hz to 100 Hz and an AC current in a high frequency range are continuously applied between the CE terminal 11CE and the WE (cur) terminal WEc to obtain AC currents of the respective frequencies. Next, while a low-frequency current or a high-frequency AC current is being passed between the CE terminal and the WE(cur) terminal, the potential difference between the RE terminal 11RE and the WE(pot) terminal and the WEp terminal is measured. The potential difference between the RE terminal 11RE and the WE(cur) terminal is measured by a potential difference meter 10V, and the measured potential difference becomes potential data in the vicinity of the measurement probe 20A, which is the measurement unit. Here, in measuring the potential data, the potential difference between the potential of the reinforcing bar R as a reference and the potential of the surface of the concrete structure C with which the measurement part of the concrete structure C, i.e., the inner electrode part (reference electrode) 22A of the measurement probe 20A, is in contact is measured.
[0055] The impedance, which is expressed as (potential difference / applied AC current), is obtained by dividing the potential difference obtained by measurement by the applied AC current, and this is performed for each frequency, and for example, an impedance spectrum is obtained by plotting the real part (Ω) on the horizontal axis and the imaginary part (Ω) on the vertical axis. The corrosion rate of the rebar can be determined by analyzing the impedance spectrum thus created.
[0056] According to the method for measuring corrosion of rebar in concrete according to the modified example of the first embodiment, the measurement probe 20 is stably attached, adhered and held in close contact with the concrete structure C, so that the workload in the measurement work can be reduced. In addition, the corrosion condition of reinforcing steel R near the underside and sides of a bridge can be stably measured, even from a ship on the sea or river surface.
[0057] The present invention is not limited to the above-described embodiment, and various modifications can be made. For example, in the above embodiment, a case has been described in which a 3.3 mol / L potassium chloride (KCl) aqueous solution is used as the supporting electrolyte aqueous solution to generate the conductive adhesive gel 26, but the present invention is not limited to a 3.3 mol / L potassium chloride (KCl) aqueous solution, and any supporting electrolyte aqueous solution such as sodium hydroxide, calcium hydroxide, or sodium sulfate that is applicable to the method for measuring corrosion of rebar in concrete may be applied, and the concentration is not limited to 3.33.3 mol / L and may be set arbitrarily.
[0058] In the above embodiment, the case where AQUALIC CS-8S (registered trademark, manufactured by Nippon Shokubai Co., Ltd.), which contains a modified acrylic cross-linked polymer, is used as the water absorbent for producing the conductive adhesive gel 26 has been described. However, the present invention is not limited to AQUALIC CS-8S (registered trademark, manufactured by Nippon Shokubai Co., Ltd.), and other water absorbents containing modified acrylic cross-linked polymers or other water absorbents not containing modified acrylic cross-linked polymers may be used.
[0059] Furthermore, in the above embodiment, the case where the conductive adhesive gel 26 and the measurement probe 20 are applied to a method for measuring rebar corrosion in concrete, which is an AC impedance method, has been described. However, the present invention is not limited to these measurement methods, and the conductive adhesive gel 26 may be applied to other methods for measuring rebar corrosion in concrete in which an AC current is applied to a concrete structural part C via the conductive adhesive gel 26 to measure the corrosion state of the internal rebar R, for example, a terminal is connected directly to the rebar, a reference electrode is placed on the concrete surface, and the potential (natural potential) from the rebar R to the concrete surface is measured to determine corrosion. [Explanation of symbols]
[0060] 1. Steel bar corrosion measuring device in concrete 10 Corrosion measuring device body 20 Measuring Probe 22 electrodes 22A Inner electrode (reference electrode) 22B Outer electrode part (counter electrode) 24 Casing 26 Conductive adhesive gel 30 Cable
Claims
1. A conductive adhesive gel containing a supporting electrolyte aqueous solution and a water-absorbent resin and having a fluidity similar to starch paste is applied to the electrodes of the measurement probe; Filling a recess in the concrete structure with a conductive adhesive gel to bring the electrode into close contact with the concrete structure and to adhere and hold the measurement probe to the concrete structure; measuring a corrosion state of the reinforcing steel in the concrete structure by passing an AC current through the electrodes to the reinforcing steel in the concrete structure; A method for measuring corrosion of rebar in concrete.
2. A method for producing a conductive adhesive gel used in the method for measuring corrosion of reinforcing bars in concrete according to claim 1, A water-absorbent resin, which acts as a gelling agent, is added to the aqueous solution of the supporting electrolyte. A conductive adhesive gel with starch paste-like fluidity is produced by stirring and kneading the supporting electrolyte aqueous solution to which the water-absorbent resin has been added. A method for producing a conductive adhesive gel comprising the steps of:
3. A conductive adhesive gel for use in the method for measuring corrosion of reinforcing bars in concrete according to claim 1, The water-absorbent resin contains a modified acrylic crosslinked polymer and has a starch paste-like fluidity. A conductive adhesive gel characterized by:
4. The water-absorbent resin is AQUALIC CS-8S (registered trademark, manufactured by Nippon Shokubai Co., Ltd.), which contains a modified acrylic crosslinked polymer. The conductive adhesive gel according to claim 3 .
5. The total weight of the measurement probe equipped with the electrodes is W (kg), and the contact area of the electrodes with the concrete structure is S (mm 2 ) when Strength T (N / mm 2 )≧9.8・(W(kg) / S(mm 2 )) is set to The conductive adhesive gel according to claim 3 .
6. The total weight of the measurement probe is 60 x 10 -3 kg, the electrode connection surface is a circle with a diameter of 50 (mm), Strength T (N / mm 2 ) ≧0.3×10 -3 (N / mm 2 ) is set to The conductive adhesive gel according to claim 5 .
7. A measurement probe for measuring a corrosion state of a reinforcing bar in a concrete structure by passing an electric current through the concrete structure, An electrode; The conductive adhesive gel according to any one of claims 3 to 6, Equipped with The conductive adhesive gel is applied to the electrodes, and the conductive adhesive gel penetrates into and adheres to the recesses of the concrete structure, and the electrodes are adhered to and held by the concrete structure. A measurement probe comprising:
Citation Information
Patent Citations
Electrochemical treatment method of concrete
JP1995286444A
Reference electrode and spontaneous potential measuring method
JP2014062782A
Corrosion detection device, corrosion detection method, and corrosion detection program
JP2020153782A
Contact type corrosion sensor
JP2021012058A
Device and method for detecting corrosion of reinforcing bars in concrete
JP7113419B2